2022
DOI: 10.1177/20503121221100136
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence in the postpartum period and its associated factors among women attending a postnatal clinic in Central Ethiopia

Abstract: Objective: Intimate partner violence may affect women at any stage of their lives, including during pregnancy and after childbirth, and can have major health consequences for both the mother and the child. Therefore, the study was aimed to assess Intimate partner violence against postpartum women and its associated factors among women attending the postpartum clinic in Central Ethiopia, 2021. Methods: The hospital based cross-sectional study design was implemented among postpartum women attending Sendafa Beke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
(92 reference statements)
1
4
0
Order By: Relevance
“…This study found that mothers whose husbands dominate the overall household decision-making authority were more likely to be violated than those who decide on their own. This was supported by the evidence obtained from the study conducted in central Ethiopia [ 28 ]. This might be because husbands who dominate decision-making power are guided by their own perspective alone, which might cause intimate partner violence.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…This study found that mothers whose husbands dominate the overall household decision-making authority were more likely to be violated than those who decide on their own. This was supported by the evidence obtained from the study conducted in central Ethiopia [ 28 ]. This might be because husbands who dominate decision-making power are guided by their own perspective alone, which might cause intimate partner violence.…”
Section: Discussionsupporting
confidence: 79%
“…This was in line with the study conducted in Ghana, which was 46% [ 15 ]. Conversely, it was higher than the study conducted in central Ethiopia at 31.4% [ 28 ], rural Zambia at 8.1% [ 14 ], Australia at 17.4% [ 11 ], Nepal at 20% [ 38 ] and South Africa at 24.56% [ 39 ]. This discrepancy might be due to the difference in the assessment method employed.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…It can cause extensive mental health consequences including depression among victims [ 8 , 9 ]. In Ethiopia, the prevalence of IPV among pregnant women was 28.74 [ 10 ] and in central Ethiopia, it was 31.4% postpartum IPV [ 11 ].…”
Section: Introductionmentioning
confidence: 99%